Rapid magnetic enrichment and sensitive detection of Sudan pollutants with nanoscale zero valent iron-based nanomaterials in combination with liquid chromatography-ultraviolet detector. (October 2021) - Zhou, Qingxiang; Zhao, Kuifu; Wu, Yalin; Li, Shuangying; Guo, Jinghan; Zhou, Boyao; Zhao, Jingyi; Guo, Libing; Chen, Chunmao
Abstract: In present work, we reported a new nanomaterial nano Fe 0 decorated with SiO2 and dopamine by self-assembly method (Fe@SiO2 @PDA). A sensitive method for determination of Sudan pollutants in aqueous samples was developed using Fe@SiO2 @PDA as magnetic solid phase extraction adsorbents prior to high-performance liquid chromatography with variable wavelength detector. The possible parameters which would affect the enrichment have been optimized. The best parameters were as follows: elutent, 4.5 mL methanol; adsorbent dosage, 30 mg; adsorption time, 20 min; elution time, 18 min; sample pH 7; sample volume, 40 mL. The experimental results demonstrated that Fe@SiO2 @PDA exhibited good adsorption properties to Sudan Red dyes. The established method provided excellent linear ranges over 0.01–50 μg L −1 and detection limits ranged from 2.0 to 5.1 ng L −1 for Sudan red I-IV. The developed method was also evaluated with real water samples and the results demonstrated that it was of applicative value owing to its merits including robustness, easy operation, fastness, cheapness and high enrichment efficiency, and had great prospect in environmental fields. Highlights: Fe@polydopamine was easily prepared and earned excellent enrichment capability. Modification with dopamine endowed nanoscale zero valent iron with new applications. Established method provided good sensitivity from 2 to 5.1 ngL −1 for Sudan I-IV. The developed method earned merits of various merits and great prospect.